PSYCHOCORRECTION TASKS IN THE SOCIALIZATION OF CHILDREN WITH AUTISM SYNDROME - Dilshoda Kuliyeva Safarovna (Лучшие интеллектуальные исследования, 2023)
Annotation: This article explores the significance of psychocorrection tasks in facilitating the socialization of children diagnosed with Autism Spectrum Disorder (ASD). Through a comprehensive literature analysis, the paper investigates existing research on psychocorrection methods, their effectiveness, and their impact on social development in children with ASD. The study also presents a detailed account of the methods employed, the results obtained, and a thorough discussion on the implications of these findings for future interventions. The article concludes with suggestions for further research and practical implications for professionals working with children on the autism spectrum.